Clinical Outcomes in a Randomized Controlled Trial Comparing Point-of-Care With Standard Human Immunodeficiency Virus (HIV) Viral Load Monitoring in Nigeria. (22nd July 2022) - Chang, Charlotte; Agbaji, Oche; Mitruka, Kiren; Olatunde, Bola; Sule, Halima; Dajel, Titus; Zee, Aaron; Ahmed, Mukhtar L; Ahmed, Isah; Okonkwo, Prosper; Chaplin, Beth; Kanki, Phyllis
Abstract: Background: Point-of-care (POC) viral load (VL) tests provide results within hours, enabling same-day treatment interventions. We assessed treatment outcomes with POC vs standard-of-care (SOC) VL monitoring. Methods: We implemented a randomized controlled trial at an urban and rural hospital in Nigeria. Participants initiating antiretroviral therapy (ART) were randomized 1:1 for monitoring via the POC Cepheid Xpert or SOC Roche COBAS (v2.0) HIV-1 VL assays. Viral suppression (VS) and retention in care at 12 months were compared via intention-to-treat (ITT) and per-protocol (PP) analyses. Post-trial surveys for POC patients and healthcare workers (HCWs) evaluated acceptability. Results: During April 2018–October 2019, 268 SOC and 273 POC patients enrolled in the trial. Viral suppression at <1000 copies/mL at 12 months was 59.3% (162/273) for POC and 52.2% (140/268) for SOC ( P = .096) in ITT analysis and 77.1% (158/205) for POC and 65.9% (137/208) for SOC ( P = .012) in PP analysis. Retention was not significantly different in ITT analysis but was 85.9% for POC and 76.9% for SOC ( P = .02) in PP analysis. The increased VS in the POC arm was attributable to improved retention and documentation of VL results. POC monitoring was preferred over SOC by 90.2% (147/163) of patients and 100% (15/15) of HCWs thought it facilitated patient care. Conclusions: POC VL monitoring did not improve 12-month VS among those with results but did improve retention and VS documentation and was preferred by most patients and HCWs. Further research can inform best POC implementation conditions and approaches to optimize patient care. Clinical Trials Registration: NCT03533868. Abstract : In a randomized controlled trial in Nigeria, point-of-care viral load monitoring improved documentation of viral suppression and retention in care at 12 months on antiretroviral therapy compared with standard monitoring and was preferred by 90.2% (147/163) of surveyed patients.